Profit: Concept and Stipulations in Islamic Commercial Debt financing - Hassanein, فياض عبد المنعم (Journal of King Abdulaziz University: Islamic Economics, 2022)
The detailed fiqh rulings on financial transaction contracts, including forward sale contracts, provide the rules, controls and characteristics of permissible commercial debt financing and clearly defines the fundamental differences between it and ribā-based debt financing. fiqh (Islamic jurisprudence) contains many rulings regarding debt, whether from sales in which the debt is deferred or from a loan or otherwise, the types, categories and degrees of such debts, as well as their strengths, weaknesses, and the causes for the legitimacy or invalidity of such transactions, the types of tricks in such transactions and the controls to prevent them, and how to avoid haram transactions and adopt halal transactions when financing by deferred debts. The forms of Islamic profit-sharing financing are divided into commutative forms (sale and lease) and partnerships in their different types. Each form has advantages, characteristics, capabilities and opportunities that enable it to meet financing needs more effectively than the others. Scientific methods need to be adopted to realize more optimal financing for financing activities in Islamic banks. For example, the form of financing through permissible debts is more appropriate than partnerships to meet the needs of customers in purchasing durable goods. In contrast, partnerships are more appropriate and effective in providing working capital in projects. The concept of profit is defined in both sales and partnerships. Profit in sales means the growth or increase that occurs through trade and exchange of goods in the markets, of which the condition lies in consent and prevention of fraud, for instance. As for profit in partnerships, it is more general, for it is the equivalent of all growth, whether in money or effort, as in establishing a partnership by mutual effort. Permissible profit represents an incentive for the growth and development of the economy; Islamic jurists say that if this incentive is absent, no one can earn a living. This permissible profit must result from actual transactions, as Sharīʿahh prohibits fictitious transactions designed to defraud through usuary-based debts. The compliance of Islamic banks to finance genuine transactions increases the confidence of their customers and the efficiency of their management and services. Also, it contributes to the competitiveness of Islamic finance in the financing market.